The Effect of Company Size, Accounting Firm Size, Solvency, Auditor Switching, and Audit Opinion on Audit Delay - Vicky Anggel Putra; Romanus Wilopo (Universitas Hayam Wuruk Perbanas, 2017)
This research aims to examine the effect of company characteristics, consisting of company size, solvency, on audit delay in the property and real estate sector companies listed on the Indonesia Stock Exchange (IDX). In addition, this research also adds three variables, i.e. accounting firm size, auditor switching and audit opinion, that are considered having an effect on audit delay,. The sample used in this research is all property and real estate sector companies listed on IDX in 2011-2015. Sampling is conducted using purposive sampling technique, with the final sample consisting of as many as 40 property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) 2011-2015. Logistic regression analysis is used to test hypotheses by explaining the relationship between the variables in this research. The results of this study show that the variables of company size, accounting firm size, solvency, and audit opinion do not have effect on audit delay, while the variable of auditor switching has a significant effect on audit delay